Determinan Kualitas Pelayanan, Keberagaman Produk dan Saluran Distribusi Terhadap Keputusan Pembelian Konsumen pada Toko Bangunan Rejeki Alam Pare - Ridwan Maliki (Jurnal Simki Economic, 2019)
Every retailer has a target to improve its business performance. To achieve the desired target, the company must be able to choose the right marketing strategy, so that the business can win in the competition. By paying attention to marketing activities are expected to influence consumer purchasing decisions. Marketing activities include product, price, place, and promotion. The four variables are combinations that have the same role and form a single unit to support the success of retail stores. Therefore, marketing activities have a very important role to inform the products offered in order to increase sales and determine consumer ratings of the goods offered. This study aims to determine and analyze 1. Quality of service affects purchasing decisions at the fortune building shop. 2. Product diversity affects purchasing decisions at the fortune building shop. 3. Distribution channels affect purchasing decisions at the fortune building shop. 4. Quality of service, product diversity, distribution channels have a joint effect on purchasing decisions at the fortune building shop. The population in this study are consumers of the natural fortune building shop. And has a sample of 40 respondents with a sample technique taken based on non-probability sampling, using an incidental sampling approach. This research is quantitative using a causal approach. The conclusion of this study states 1. The quality of service has a significant effect on consumer purchasing decisions at the fortune building shop in Pare District.2. Product diversity has a significant effect on consumer purchasing decisions at a fortune building shop in Pare District. 3. Distribution channels have a significant effect on consumer purchasing decisions at the fortune building shop in Pare District. 4. Service Quality, Product Diversity and Distribution Channels simultaneously have a significant effect on purchasing decisions.